The Proportion of Meniscus Tears Considered Repairable, and Thus Repaired, Increased During a Single Surgeon’s Practice of 20 Years - Alejandro Espejo-Reina, M.D., M.Sc.; Enrique Sevillano-Pérez, M.D., M.Sc.; María Josefa Espejo-Reina, M.D., M.Sc.; Maximiano Lombardo-Torre, M.D., M.Sc.; Ana Pérez-Blanca, D.Eng.; Alejandro Espejo-Baena, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2023)
Purpose: The purpose of this study was to evaluate practice patterns of a single surgeon with respect to meniscectomy and meniscal repair over a 20-year period at a single institution. Methods: A cross-sectional descriptive study was carried out by reviewing the surgical data from the past 20 years (2002-2021) of patients who underwent arthroscopic primary meniscal surgery. Age, sex, knee and meniscus affected, morphology of the meniscal tear, meniscal radial location, location on the axial plane, tissue quality, and associated injuries were recorded. An analysis of the evolution of the characteristics of the meniscal lesions was performed according to the presence of degenerative tissue, the repairability of the lesion, and the treatment performed. Categorical data were represented in contingency tables and compared using the χ2 test for significance of differences, which was set at P < .05. Results: In total, 1,892 cases were included. A decrease in degenerative meniscal tears was found, from 63.2 in 2002 to 2006 to 9.7% in 2017 to 2021 (P < .001), while repairable tears increased from 1.6% to 82.3% P < .001); in the same periods, arthroscopic partial meniscectomy procedures declined from 75.7% to 17.7% (P < .001) while meniscal repair increased from 0.4% to 81.3% (P < .001). All types of tears increased significantly their repairability, although longitudinal tears, root tears, and ramp lesions showed the highest possibilities for repair. Conclusions: In the present study, a drastic change in the attitude toward meniscal preservation in the past 20 years was observed, with a large increase in the proportion of tears considered repairable found in primary arthroscopic surgery (to 80% of cases) and a decrease in degenerative meniscus tears (to less than 10%). Clinical Relevance: In the past 2 decades, arthroscopic knee surgery has evolved such that more meniscus tears are deemed repairable, and fewer tears considered degenerative are indicated for arthroscopy.